The Role of Local Political Parties in Shaping Electoral Outcomes in Makassar City - Ardiyanti, Ardiyanti; Nadila, Nidya; Dipanegara, Romy (Journal Social Civilecial, 2024)
The analysis investigates how local political parties affect electoral results in Makassar City through evaluations of their strategies together with voter response patterns and social community processes. Through a qualitative method researchers conducted semi-structured interviews combined with focus group sessions and document evaluation to understand the voter-party interactions and local strategy development and community network use in Makassar City. Local parties operating in Makassar depend on direct contact with citizens together with connections to local leadership groups for establishing contact and voter participation. Electoral choices of voter’s stem from concrete needs including improvements in infrastructure and local service delivery instead of national political perspectives. Local political campaigns have shown a need for ethnic-specific approaches which create campaign messaging that targets particular cultural and ethnic groups. Local political parties practice strategic autonomy to create custom-made political strategies which adapt to specific local socio-political conditions apart from national political parties. The study fills knowledge gaps within Indonesian political research by documenting how local actors evolve their political tactics which influences election results. This study explains significant information to those who study local politics including policymakers’ analysts and academic researchers of electoral dynamics.